THE ANALYSIS OF ACCOUNTING INFORMATION SYSTEM SERVICE REVENUE CYCLE OF INSTALLING PREPAID ELECTRICITY (TOKEN) (Case Study at PT PLN (Persero) of East Java Distribution for Malang Area) - Rachmawanty, Beuthy; Ekowati, Wiwik Hidajah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this research is to analyse the accounting information system revenue cycle of installing a prepaid electricity that is applied by PT PLN (Persero) Distribution East Java Area Malang. Service revenue cycle of installing prepaid electricity begins from new customer to register prepaid electricity, then the PLN to conduct electricity meter installation until the light is on. The type of research is a qualitive research, which the research to develop a concept and gather avalaible facts but not using hypothesis testing. The goal is to provide an overview of the current existingsituation and circumstances. The data obtained through interviews and documentation. The result of this research is then evaluated and given an improved solution for any given problem. The result of the analysis concludes in general had the implementation of accounting information systems and intern control in the revenue cycle of installation prepaid electricity has been maintained by PT PLN (Persero) Distribution East Java Area Malang perfectly, which is in accordance with standards procedures determined by the company. The system used is computer based, which is System Application and Product in Data Processing (SAP). There are few weaknesses in the implementation of prepaid electricity system. The disadvantage is that customer must report to PLN office to seek an assistance to top up electricity credit due to power meter often damaged/eror, sales of physical voucher are not available when customer top up electricity credit, and the difficulty of checking electricity bill online through www.pln.co.id. Weaknesses that should be corrected immediately to one of the company’s value is sensitive to the needs of customer can be realized by the company. Keyword: Prepaid Electricity, Accounting Information System, Internal Control, Service Revenue of Installing Prepaid Electricity Internal Control, and SAP.